Combined Immunodeficiency With Late-Onset Progressive Hypogammaglobulinemia and Normal B Cell Count in a Patient With RAG2 Deficiency - Dorna, Mayra B.; Barbosa, Pamela F. A.; Rangel-Santos, Andréia; Csomos, Krisztian; Ujhazi, Boglarka; Dasso, Joseph F.; Thwaites, Daniel; Boyes, Joan; Savic, Sinisa; Walter, Jolan E. (Frontiers in Pediatrics, 2019)
Proteins expressed by recombination activating genes 1 and 2 (RAG1/2) are essential in the process of V(D)J recombination that leads to generation of the T and B cell repertoires. Clinical and immunological phenotypes of patients with RAG deficiencies correlate well to the degree of impaired RAG activity and this has been expanding to variants of combined immunodeficiency (CID) or even milder antibody deficiency syndromes. Pathogenic variants that severely impair recombinase activity of RAG1/2 determine a severe combined immunodeficiency (SCID) phenotype, whereas hypomorphic variants result in leaky (partial) SCID and other immunodeficiencies. We report a patient with novel pathogenic compound heterozygous RAG2 variants that results in a CID phenotype with two distinctive characteristics: late-onset progressive hypogammaglobulinemia and highly elevated B cell count. In addition, the patient had early onset of infections, T cell lymphopenia and expansion of lymphocytes after exposure to herpes family viruses. This case highlights the importance of considering pathogenic RAG variants among patients with preserved B cell count and CID phenotype.